A Review of The Concept and Application of Geospatial Technology in Mapping and Modeling the Migration of Whale Shark (Rinchodon typus) - Thomas Frans Pattiasina (Musamus Fisheries and Marine Journal, 2020)
The Whale Shark (Rinchodon typus) is a species of pelagic fish with the largest size in the world and has a very wide range of movements. By understanding the migration of whale sharks a number of important policies can be immediately applied to preserve the population of this species in nature. This paper aims to provide an overview of the concept and application of spatial science and technology to map and model the migration of whale shark species. This paper is the result of a review of various literatures, both scientific journal articles and books related to mapping and modeling of common marine animals and whale sharks in particular. The paper begins with a description of the bioecological aspects and threats to the whale shark population. Furthermore, the concept of mapping and modeling of whale shark migration will be described, covering important factors in mapping and modeling, development of marine geographic information migration model (GIS) and application of whale shark migration modeling. The conclusion from the review is that bioecological characteristics and patterns of whale shark migration cause these species to be vulnerable to various threats from both natural factors and human activities. Migration mapping and modeling is generally based on environmental variation or oceanographic factors and species movement types. Accurate mapping and modeling results will be of great value in planning and policies regarding the management and conservation of whale shark species.